FINANCIAL SUSTAINABILITY INTHE ASSESSMENT OF THEFINANCIAL PERFORMANCE OF WEST SUMATRA SHARIA FINANCING BANK (BPRS) - Nasfi, Nasfi; Iska, Syukri; Nofrivul, Nofrivul; Antoni, Antoni (Jurnal Menara Ekonomi : Pelatihan dan Kajian Ilmiah Bidang Ekonomi, 2019)
The objective of research to examine the financial performance of the Bank Financing of Islamic People of West Sumatra. Data analysis techniques using the BPRS health assessment applicable in accordance with the decision of Bank Indonesia No. 9/17/PBI/2007 dated December 4, 2007, the financial aspects of the form CAR, FDR, NPF, ROA and BOPO. Results of the study found that the ratio of CAR, BPRS West Sumatera amounting to 14.27%, with